Removal of Heavy Metal Ions From Aqueous Solutions Using Bacillus subtilis Biomass Pre‐Treated by Supercritical Carbon Dioxide. Issue 10 (18th September 2017) - Al‐Gheethi, Adel; Mohamed, Radin; Noman, Efaq; Ismail, Norli; Kadir, Omar Ab.
Abstract : Surface properties of bacterial cells enable them to be used in the removal of heavy metals. Moreover, the inactivation of bacterial cells via chemical or physical processes may enhance the biosorption efficiency for heavy metals. The use of supercritical carbon dioxide (SC‐CO2 ) to inactivate bacteria based on destruction of cell walls took place due to the pressurized CO2 . In this study, the pre‐treatment of Bacillus subtilis cells by SC‐CO2 (BM1), steam autoclaving (BM2), and untreated living cells (BM3) were investigated to show improvement in heavy metal removal. The removal process was optimized based on the main factors affecting bacterial biosorption, which included heavy metals ion concentrations, cell biomass concentrations, pH, time, and temperature. The efficiency of bacterial biomass in removing Ni 2+ ions in the presence of different concentrations of Pb 2+, Cu 2+, Zn 2+, and Cd 2+ was also tested. BM1 and BM2 exhibited the highest potential for the removal of nickel ions in comparison to BM3. The maximum efficiency was 98.54, 99.2, and 96.3% for BM1, BM2, and BM3, respectively. Moreover, BM1 displayed a higher biosorption capacity for Ni 2+, Cu 2+, Zn 2+, Pb 2+, and Cd 2+ (>150 mg g −1 ) than BM2 and BM3. Biosorption on bacterial cell biomass of Ni 2+ ions shows lower removal affinity in the presence of other metal ions. In conclusion, the pre‐treatment of bacterial cells biomass by SC‐CO2 enhanced the removal process of heavy metal ions compared to untreated living cells. Abstract : Bacterial cells biomass pre‐treated by supercritical CO2 exhibits more removal efficiency for heavy metal ions than untreated cells. This may be due to the mechanism of supercritical CO2, leading to a destruction of bacterial cell membranes with higher affinity to biosorb metal ions.